Rural community "Santa Maria del Loreto". 20 years with photovoltaic solar energy - Cuán, José Emilio Camejo; Fuentes, Fernando Hechavarría; Heredia, Rubén Ramos; Yero, Roger Anner Proenza (IJRDO-Journal of Applied Science, 2019)
The work exposes the most significant and relevant aspects, in the 20 years of the start-up of the AutonomousPhotovoltaic Solar Power Plant of the Rural Community "Santa Maria del Loreto" which constitutes, in our opinion,challenge and the greatest lesson learned, taking into account that it demonstrated at this time the technical,economic, social and sustainability viability, from a specialized follow-up by specialists in the subject and communityparticipation.